Carbon-coated nanowire network electrodes

JP2025506714APending Publication Date: 2025-03-13FUNDACION IMDEA MATERIALES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024548665
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-02-18
Filing Date
2023-02-17
Publication Date
2025-03-13

AI Technical Summary

Benefits of technology

【0007】 さらに、本発明の炭素系コーティングで被覆されたナノワイヤのネットワークを含む電極は、セルで試験された場合に、低レートで、そして高面積密度であってさえ理論容量に近い値を示した。加えて、前記電極は、高い比容量、高い構造安定性、および高い容量保持率とサイクル性を示している。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025506714000001
    Figure 2025506714000001
  • Figure 2025506714000002
    Figure 2025506714000002
  • Figure 2025506714000003
    Figure 2025506714000003
Patent Text Reader

Abstract

The present invention refers to a method for preparing an electrode; to the electrode obtainable by said method; to a cell containing the electrode; and to the use of the electrode.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the preparation of an electrode. More specifically, the present invention relates to a process for preparing an electrode for a battery and to the electrode obtained by said process. [Background technology]

[0002] Electrochemical energy generation and storage is a promising technology for powering electric vehicles and modern society's devices. The development of new types of electrodes is believed to be necessary to increase the energy density of batteries relative to conventional lithium-ion batteries.

[0003] Networks of nanowires offer advantages over materials made from larger components. Generally, nanowires are mechanically flexible due to their nanoscale dimensions and have a reduced amount of defects compared to bulk materials. They also exhibit a variety of properties as a result of their small size and one-dimensional morphology. As a result, some of the properties of nanowire networks depend on the properties of the nanowires.

[0004] The document WO2021094485 discloses an electrode comprising a network of nanowires and, optionally, an electrical connection or current collector. According to the document, the mechanical properties imparted by the nanowire network obviate the use of reinforcing additives (e.g., polymer binders) in the electrode, and allow for methods of processing or integrating such electrodes without the need for solvents or other forms of dispersion as previously used. However, this type of electrode has low electrical conductivity values, and therefore low capacity as an electrode in a battery, especially at high charge / discharge rates, and poor retention of said capacity under repeated charge / discharge cycles (often referred to as cyclability).

[0005] Despite various proposals in the art, there exists a need to develop methods for synthesizing new electrodes and new electrodes with good mechanical and electrochemical properties (such as capacity and cyclability properties) that overcome the limitations of the prior art. Summary of the Invention [Means for solving the problem]

[0006] The inventors of the present invention have found a method for producing an electrode comprising a network of nanowires coated with a carbon-based coating. This method of producing an electrode produces a network of nanowires that is self-supporting and has good mechanical properties, such as good flexibility in bending, and in which the aspect ratio of the nanowires is high. In addition, the method is capable of coating the nanowire network with a uniform carbon-based coating layer, providing high electrical conductivity values ​​leading to high capacity and cyclability. Furthermore, the method of the present invention is based on aerosol and gas phase techniques, which allows for a high level of process control and the possibility of scaling up to large quantities of product. In addition, the carbon-based coating layer of the electrode of the present invention contains crystalline graphitic domains that improve the electrochemical properties of the electrode, in particular its electrical conductivity. Furthermore, the authors have confirmed that the interface between the nanowires of the network and the carbon coating contains mainly aligned crystalline graphitic domains. This feature is a consequence of the carbopyrolytic deposition step of the electrode synthesis method, which improves the final properties of the electrode.

[0007] Moreover, electrodes comprising a network of nanowires coated with the carbon-based coating of the present invention have demonstrated near theoretical capacity when tested in cells even at low rates and high areal densities, and have demonstrated high specific capacitance, high structural stability, and high capacity retention and cyclability.

[0008] Thus, in a first aspect, the present invention provides a method for producing a composition comprising: (a)i. providing a first gas stream to a reaction vessel; the first gas flow comprises at least one precursor compound comprising at least one element selected from Si, Ge, Al, Cu, Zn, Sb, Ni, Ti, Se, Ta, Pt, Mo, V, W, Co, Mn, and Li; and the at least one precursor compound is a metal hydride or an organometallic compound; ii. providing a second gas stream to the reaction vessel, the second gas stream comprising metallic catalyst particles; the first and second gas streams mixing in the reaction vessel to form a gas stream mixture; the metallic catalyst particles comprising one or more elements selected from Au, Ag, Cu, Fe, Ni, Ga, Co, Pt, In, and Al; and producing a network of nanowires by a method comprising: at least one precursor compound is present in the gas stream mixture in a mole fraction (xi) of at least 0.010; The temperature in the reaction vessel is in the range of 200 to 3000°C; at least one precursor compound decomposes under temperature in the reaction vessel and grows on the metallic catalyst particles by vapor-liquid-solid (VLS) and / or chemical vapor deposition (CVD) to form a network of nanowires; (b) coating the network of nanowires obtained from step (a) by pyrolysis of a carbon precursor at a temperature between 500° C. and 1300° C. under an inert gas atmosphere to obtain a network of nanowires coated with a carbon coating; (c) optionally contacting the network of nanowires coated with the carbon coating with an electrical connection or current collector; The present invention is directed to a method of preparing an electrode, comprising:

[0009] In a second aspect, the present invention provides a method for producing a pharmaceutical composition comprising the steps of: - a network of nanowires coated with a carbon coating; the network of nanowires has a nanowire aspect ratio of at least 130; the carbon coating comprises graphitic carbon; a network of nanowires, the carbon coating being in an amount greater than 3 wt.% of the total weight of the network of nanowires coated with the carbon coating; - optionally electrical connections and / or current collectors, The present invention is directed to an electrode obtainable by the method of any of the detailed embodiments of the method of the present invention, including

[0010] In a further aspect, the present invention provides a method for producing a method for treating a cancer cell comprising: - electrodes, at least one of which is according to any of the embodiments of the present invention; - electrolytes; - a means for connecting to a power / load source; Target cells that contain

[0011] A further aspect of the invention is directed to the use of the electrode of the invention in any of its detailed embodiments in a battery, preferably a lithium battery. [Brief description of the drawings]

[0012] [Figure 1] Figure 1 shows images of a free-standing Si nanowire network before (a) and after (b) carbon coating. [Diagram 2] FIG. 2 shows an electron micrograph of the Si nanowire network before carbon coating. [Diagram 3] FIG. 3 shows a HRTEM micrograph of the interface between the carbon coating and the crystalline Si of the Si nanowire network after carbon coating. [Figure 4] FIG. 4 shows a representative Raman spectrum showing the crystallinity of the Si nanowires and the graphitization of the coating on the C-coated Si nanowire network. [Diagram 5] FIG. 5 shows the XRD pattern of the Si nanowire network after carbon coating. [Figure 6]Figure 6 shows (a) the voltammograms of the first 10 cycles at a scan rate of 0.025 mV / s and (b) the rate performance (specific capacity vs. cycle number) at C rates from C / 20 to 2C obtained using Si nanowire networks coated with carbon coatings (two different carbon contents: 27% and 5% by weight, respectively) as electrodes in a half-cell. The results for the Si nanowire networks coated with 27 wt% carbon coating are shown as solid circles and those for the Si nanowire networks coated with 5 wt% carbon coating are shown as triangles. Electrode mass loading: 1.2 mg / cm2, and 1C=3.6 A / g. [Figure 7] Figure 7 shows (i) the specific capacitance versus cycle number and (ii) coulombic efficiency of carbon-coated Si nanowire networks as electrodes at C-rates of (a) 100 cycles at C / 10 and (b) 500 cycles at C / 2 (1C = 3.6 A / g). [Figure 8] Figure 8 shows the rate performance (specific capacity vs. cycle number) at C rates from C / 20 to 2C obtained using carbon-coated Si nanowire networks (filled circles) and results for Si nanowire networks with interspersed carbon nanotubes (shown as squares). Electrode mass loading: 1.2 mg / cm2, and 1C = 3.6 A / g. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] The present invention refers to a method for preparing an electrode, the electrode obtainable by said method, a battery cell comprising the electrode, and the use of the electrode.

[0014] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this disclosure belongs. As used herein, the singular forms "a," "an," and "the" include plural referents unless the context clearly dictates otherwise.

[0015] In a first aspect, the present invention provides a method for producing a method for treating a cancer cell comprising: (a)i. providing a first gas stream to a reaction vessel; the first gas flow comprises at least one precursor compound comprising at least one element selected from Si, Ge, Al, Cu, Zn, Sb, Ni, Ti, Se, Ta, Pt, Mo, V, W, Co, Mn, and Li; and the at least one precursor compound is a metal hydride or an organometallic compound; ii. providing a second gas stream to the reaction vessel, said second gas stream comprising metallic catalyst particles; mixing the first and second gas streams in the reaction vessel to form a gas stream mixture; the metallic catalyst particles comprise at least one element selected from Au, Ag, Cu, Fe, Ni, Ga, Co, Pt, In, and Al; and producing a network of nanowires by a method comprising: at least one precursor compound is present in the gas stream mixture in a mole fraction (xi) of at least 0.010; The temperature in the reaction vessel is in the range of 200 to 3000°C; at least one precursor compound decomposes under temperature in the reaction vessel and grows on the metallic catalyst particles by vapor-liquid-solid (VLS) and / or chemical vapor deposition (CVD) to form a network of nanowires; (b) coating the network of nanowires obtained from step (a) by pyrolysis of a carbon precursor at a temperature between 500° C. and 1300° C. under an inert gas atmosphere to obtain a network of nanowires coated with a carbon coating; (c) optionally contacting the network of nanowires coated with the carbon coating with an electrical connection or current collector; The present invention is directed to a method of preparing an electrode, comprising:

[0016] Step (a) The method of preparing a network of nanowires may include the further step of converting the network of nanowires into a fibre, yarn or fabric, optionally performed simultaneously with step (ii) of the method.

[0017] Step (i) The method of preparing a network of nanowires of the present invention comprises the step (i) of supplying a first gas flow to a reaction vessel, said first gas flow comprising at least one precursor compound comprising at least one element selected from Si, Ge, Al, Cu, Zn, Sb, Ni, Ti, Se, Ta, Pt, Mo, V, W, Co, Mn, and Li, and wherein the at least one precursor compound is a metal hydride or an organometallic compound.

[0018] In one embodiment, the first gas flow comprises a sheath gas selected from nitrogen, hydrogen, a noble gas, and mixtures thereof; preferably H 2 or inert gas, specifically N 2 Further includes:

[0019] In one embodiment, the first gas flow comprises at least one precursor compound and a sheath gas selected from nitrogen, hydrogen, a noble gas, and mixtures thereof; preferably H. 2 or inert gas, specifically N 2 It consists of:

[0020] Precursor Step (i) of the method of the present invention comprises providing a first gas stream to a reaction vessel, said first gas stream comprising at least one precursor compound.

[0021] In particular embodiments, the at least one precursor compound is a compound that participates in a reaction (i.e., a chemical reaction) that produces the nanowire network of the present invention, such as, for example, SiH 4 is a precursor compound that can result in a Si nanowire network when used in the method of the present invention.

[0022] In particular embodiments, at least one precursor compound of the method of the present invention comprises at least one element selected from Si, Ge, Al, Cu, Zn, Pt, Mo, V, W, Co, Mn, and Li; particularly Si, Ge, Al, Cu, Zn, Pt, and Co; more particularly Si and Ge; and even more particularly Si.

[0023] In one embodiment, the metal element of the metal hydride or organometallic compound of at least one precursor compound is at least one element selected from Si, Ge, Al, Cu, Zn, Sb, Ni, Ti, Se, Ta, Pt, Mo, V, W, Co, Mn, and Li; preferably, Si, Ge, Al, Cu, Zn, Pt, Mo, W, Co, Mn, and Li; particularly, Si, Ge, Al, Cu, Zn, Pt, and Co; more particularly, Si, Ge, and Al; even more particularly, Si and Ge; and even more particularly, Si. In a preferred embodiment, the metal element of the metal hydride or organometallic compound of at least one precursor compound is an element selected from Si, Ge, Al, Cu, Zn, Sb, Ni, Ti, Se, Ta, Pt, Mo, V, W, Co, Mn, and Li; preferably, Si, Ge, Al, Cu, Zn, Pt, Mo, W, Co, Mn, and Li; particularly, Si, Ge, Al, Cu, Zn, Pt, and Co; more particularly, Si, Ge, and Al; and even more particularly, Si and Ge.

[0024] The precursors of the present invention include (3-aminopropyl)triethoxysilane, N-sec-butyl(trimethylsilyl)amine, chloropentamethyldisilane, tetramethylsilane, silicon tetrabromide, silicon tetrachloride, tris(tert-butoxy)silanol, or SiH 4compounds containing Si such as tetramethylgermanium, triethylgermanium hydride, triphenylgermanium hydride, triphenylgermanium hydride, tetramethylgermanium, tributylgermanium hydride, triethylgermanium hydride, triphenylgermanium hydride; compounds containing Ge such as dimethylselenide; compounds containing Al such as trimethylaluminum (TMAl) or triethylaluminum (TEAl); but are not limited to these.

[0025] The at least one precursor compound may be in solid or liquid form (i.e., aerosolized in the first gas stream of the method of the present invention), or in gas form. In a detailed embodiment, the at least one precursor compound is in gas form.

[0026] In more particular embodiments, the at least one precursor compound is a metal hydride, particularly SiH 4 It is.

[0027] In particular embodiments, the at least one precursor compound is one precursor compound.

[0028] In a detailed embodiment, the first gas flow includes two or more precursor compounds. In particular, the first gas flow may include a first precursor compound and an additional precursor compound. In a detailed embodiment, the additional precursor compound may be used as a dopant for the nanowire network (in a smaller amount than the main precursor compound). The suitable dopant depends on the nanowire material being doped.

[0029] In a detailed embodiment, at least one precursor compound of the present invention is provided to a reaction vessel of the present invention at a flow rate of at least 0.01 mol / h; preferably at a flow rate of at least 0.05 mol / h; more preferably at a flow rate of at least 0.10 mol / h; even more preferably at a flow rate of about 0.03 mol / h.

[0030] Step (ii) The method of preparing a network of nanowires in step (a) includes step (ii) of providing a second gas stream to a reaction vessel, the second gas stream comprising metallic catalyst particles; and the first and second gas streams mix in the reaction vessel to form a gas stream mixture.

[0031] In one embodiment, the second gas flow is a sheath gas selected from nitrogen, hydrogen, a noble gas, and mixtures thereof; preferably H 2 or inert gas, specifically N 2 Further includes:

[0032] In one embodiment, the second gas flow comprises metallic catalyst particles and a sheath gas selected from nitrogen, hydrogen, a noble gas, and mixtures thereof; preferably H. 2 or inert gas, specifically N 2 It consists of:

[0033] In a particular embodiment, only one type of gas is used in the present invention. In particular, the terms "first" and "second" refer to the number of streams used.

[0034] In a particular embodiment, step (a) of the method of preparing a network of nanowires includes the further step of recovering the network of nanowires; in particular, recovering the network of nanowires by spinning (as a yarn or fabric) and winding it onto a bobbin.

[0035] catalyst In a detailed embodiment, the metallic catalyst particles of the method of the present invention comprise one or more elements selected from Au, Ag, Cu, Fe, Ni, Ga, Co, Pt, In, and Al; in particular, one or more elements selected from Au, Ni, Ag, and Cu; more particularly, one or more elements selected from Au and Ag; and even more particularly, Au. The metallic catalyst particles may consist of a single element or a combination (e.g., an alloy) of two or more elements. The metallic catalyst particles may be present in the second gas stream as solid particles or as liquid particles; preferably as solid particles.

[0036] In another detailed embodiment, the metallic catalyst particles of the method of the invention further comprise one or more additional elements selected from the group 16 elements that control and / or promote nanowire growth, the additional elements being specifically selected from oxygen, sulfur, selenium, tellurium, and polonium; more specifically selected from S, Se, Te, and O.

[0037] In particular embodiments, the metallic catalyst particles consist of an element selected from Au, Ag, Cu, Fe, Ni, Ga, Co, Pt, In, and Al; particularly, they consist of an element selected from Au, Ag, and Cu; more particularly, they consist of an element selected from Au and Ag; and even more particularly, they consist of Au.

[0038] In a detailed embodiment, the metallic catalyst particles have an average diameter between 0.1 and 100 nm; preferably between 1 and 30 nm. The average diameter of the metallic catalyst particles of the present invention may be calculated from the average of values ​​obtained by measuring the diameter of more than 100 metallic catalyst particles using electron micrographs, or from size distributions obtained from different aerosol measurement techniques such as differential electrostatic classification (DMA).

[0039] Additionally, the metallic catalyst particles may be uncharged or the metallic catalyst particles may be imparted with a charge.

[0040] The metallic catalyst particles may be provided to the reaction vessel in the form of an aerosol generated by an upstream aerosol generating device. Alternatively, the metallic catalyst particles may be formed in situ by providing a precursor compound; preferably a gaseous precursor compound. In a preferred embodiment, the metallic catalyst particles are provided in the form of an aerosol.

[0041] In a detailed embodiment, the metallic catalyst particles have a molecular weight of at least 1×10 -5 g / h; preferably at least 1 x 10 -4 g / h; more preferably at least 2 x 10 -4 g / h; more preferably at least 2.7 x 10 -4 The reaction vessel is charged at a flow rate of 100 g / h.

[0042] Gas Stream Mixture In a detailed embodiment, the gas stream mixture is generated when the first and second gas streams contact in the reaction vessel. A mixing means may be used to mix the streams to form the gas stream mixture. If necessary, pressure and flow rate may be adjusted to ensure proper mixing of the first and second streams to form the gas stream mixture.

[0043] In a detailed embodiment, the gas stream mixture circulates through the reaction vessel at a flow rate of at least 60 liters / h; preferably at least 120 liters / h.

[0044] In another detailed embodiment, the gas flow mixture has a residence time in the reaction vessel of less than 100 seconds; specifically between 0.1 and 80 seconds; more specifically between 1 and 60 seconds; even more specifically between 2 and 30 seconds; preferably between 4 and 16 seconds.

[0045] In addition to the gas stream mixture, one or more sheath streams may be introduced into the reaction vessel of the present invention, including, but not limited to, nitrogen, hydrogen, and noble gases such as helium and argon.

[0046] In the method of the present invention, the at least one precursor compound is present in the gas stream mixture in a mole fraction (xi) of at least 0.010.

[0047] In particular embodiments, the at least one precursor compound is present in the gas stream mixture at a molar fraction of at least 0.012; preferably at least 0.015; more particularly between 0.01 and 0.5; preferably between 0.015 and 0.400; more preferably between 0.016 and 0.100; more preferably about 0.02. In the context of the present invention, a mole fraction is expressed as the amount (in moles) of a component divided by the total amount of all components (also expressed in moles).

[0048] In a particular embodiment, at least one precursor compound of the present invention is at least 0.1×10 -4 in mol / l; specifically, at least 1 × 10 -4 at a concentration of at least 1.5 × 10 -4 at a concentration of at least 2 × 10 -4 It is present in the gas stream mixture in a concentration of mol / l.

[0049] In a detailed embodiment, the gas stream mixture comprises H 2 Includes.

[0050] In one embodiment, the gas stream mixture of the process of the present invention comprises: - at least one precursor compound; - with at least a sheath gas such as nitrogen, hydrogen and / or a noble gas; - metallic catalyst particles; Includes.

[0051] In one embodiment, the gas stream mixture of the process of the present invention comprises: - at least one precursor compound; - with at least a sheath gas such as nitrogen, hydrogen and / or a noble gas; - metallic catalyst particles; It consists of:

[0052] In a preferred embodiment, the gas stream mixture of the process of the present invention comprises: - a precursor compound which is a metal hydride or an organometallic compound; the metal element of the metal hydride or organometallic compound is selected from Si, Ge, Al, Cu, Zn, Sb, Ni, Ti, Se, Ta, Pt, Mo, V, W, Co, Mn and Li; preferably, Si, Ge, Al, Cu, Zn, Pt, Mo, V, W, Co, Mn and Li; in particular, Si, Ge, Al, Cu, Zn, Pt and Co; more particularly, Si, Ge and Al; even more particularly, Si and Ge; and even more particularly, Si; - with a sheath gas or gas mixture, such as nitrogen, hydrogen, a noble gas, or a combination thereof; - metallic catalyst particles consisting of one element selected from Au, Ag, Cu, Fe, Ni, Ga, Co, Pt, In and Al; in particular consisting of one element selected from Au, Ag and Cu; more particularly consisting of one element selected from Au and Ag; and even more particularly consisting of Au; It consists of:

[0053] Reaction vessel In a detailed embodiment, the reaction vessel used in the process of step (a) is a gas reaction vessel; preferably a cylindrical reaction vessel; more preferably a cylindrical reaction vessel made of ceramic or metal; even more preferably a cylindrical reaction vessel made of stainless steel, such as a tube.

[0054] According to the method of the present invention, the first and second gas streams are mixed in a reaction vessel.

[0055] In particular embodiments, the temperature inside the reactor vessel is uniform; particularly uniform within 50 degrees along the reactor tube, more particularly uniform over 80 cm from the hot zone; particularly uniform between 30 and 50 cm of the hot zone.

[0056] In step (a) of the process of the present invention, the temperature in the reaction vessel is in the range of from 200 to 3000°C; preferably the temperature is in the range of from 300 to 2800°C, more preferably the temperature is in the range of from 400 to 2000°C, even more preferably the temperature is in the range of from 500 to 1800°C.

[0057] In a detailed embodiment, the pressure in the reaction vessel is between 500 mbar and 20000 mbar (50000 Pa and 2000000 Pa); preferably between 900 mbar and 3000 mbar (90000 Pa and 300000 Pa).

[0058] In particular embodiments, the temperature within the reaction vessel is achieved by any suitable heating means known in the art; preferably by plasma, arc discharge, resistive heating, hot wire heating, torch heating, or flame heating means; more preferably by resistive heating, hot wire heating, torch heating, or flame heating means.

[0059] Growth of nanowire networks In step (a) of the method of the present invention, at least one precursor compound decomposes under temperature conditions in a reaction vessel and is grown on the metallic catalyst particles by a vapor-liquid-solid (VLS) and / or chemical vapor deposition (CVD) process to form a network of nanowires. In a detailed embodiment, the nanowires are grown while in the gas flow mixture (i.e., they are aerosolized). In a detailed embodiment, at least one precursor compound decomposes under temperature conditions in a reaction vessel and is grown on the metallic catalyst particles by a floating catalyst chemical vapor deposition (CVD) process to form a network of nanowires.

[0060] If necessary, one or more sheath flows may be introduced into the reaction vessel, in particular between the gas flow mixture and the wall of the reaction vessel.

[0061] By selecting the appropriate precursor compounds, gas flows, temperatures, pressures, and metallic catalyst particles, nanowires can be grown axially, or radially, or in a combination of these two growth modes; preferably, growth occurs in the axial direction; more preferably, growth occurs in the 110 direction; particularly in the case of Si nanowires.

[0062] The growth of the nanowires may be initiated by catalytic decomposition of at least one precursor compound on the surface of the metallic catalyst particles and nucleation of the nanowires on the surface of the metallic catalyst particles. After nucleation, the nanowires may undergo directional growth to form elongated objects, i.e., nanowires. Growth may occur through a vapor-liquid-solid (VLS) method and / or a chemical vapor deposition (CVD) method. At the same time, the nanowires reach a critical concentration and aggregate to form a network of nanowires in the reaction vessel. Thus, the method of the present invention is a continuous aggregation method. Preferably, a gas mixture carrying the metallic catalyst particles flows through the reactor, and the nanowire network flows through the length of the reaction vessel. In one embodiment, the network of nanowires includes hollow nanowires, such as nanotubes. In one embodiment, the network of nanowires includes hollow nanowires and solid nanowires, such as solid nanowires. In another embodiment, the network of nanowires consists of hollow nanowires, such as nanotubes.

[0063] In the context of the present invention, the expression Chemical Vapor Deposition (CVD) is understood as a process in which one or more volatile precursor compounds react and / or decompose on a catalyst surface to produce one-dimensional structures, such as nanowires. The catalyst particles may be suspended in the gas phase and are generally referred to as suspended catalysts. The particles may be in a molten or solid state and may contain additional elements that control and / or promote the growth of nanowires, as described herein above. These additional elements include group 16 elements, such as S, Se, Te, or oxygen. The precursors may also partially decompose on the reactor surface.

[0064] In a detailed embodiment, the method for preparing a network of nanowires of the present invention comprises the step of: -7 Specifically, the aerogelation parameters are at least 1 × 10 -6 More specifically, under the aerogelation parameters of at least 2 × 10 -6 The aerogelation is carried out under the following aerogelation parameters:

[0065] In the context of the present invention, the expression "aerogelation parameter" is understood as the product of the average aspect ratio (length / diameter) of the nanowires and the volume concentration (vc (volume of nanowires / volume of reactor)).

[0066] In the context of the present invention, the expression "vapor-liquid-solid" (VLS) method is a mechanism for growing one-dimensional structures, e.g. nanowires, from chemical vapor deposition by direct adsorption of a gas (i.e. at least one precursor compound in the vapor phase) onto liquid catalyst particles that can rapidly adsorb the vapor to supersaturation levels, from which crystal growth can occur from nucleated seeds at the gas-liquid-solid interface.

[0067] In a particular embodiment, a nanowire network is formed while present in the gas flow mixture (in the reaction vessel), and in particular a network of nanowires in which the nanowires are aggregated (i.e., the nanowires are joined, entangled, connected or fused with each other) is obtained at the outlet of the reaction vessel of the present invention.

[0068] In a detailed embodiment, the network of nanowires is produced as a continuous process. Alternatively, the network of nanowires can be produced individually. In a preferred embodiment, the network of nanowires is produced continuously.

[0069] In a detailed embodiment, the method of step (a) further comprises the step of collecting the network of nanowires on a substrate; and preferably, the substrate is a filter; more preferably, a vacuum filter. In a more detailed embodiment, the method further comprises the step of densifying the network of nanowires; preferably, by using a solvent or mixture of solvents; more preferably, an organic solvent or mixture of organic solvents; even more preferably, a solvent or mixture of solvents containing an alcohol group; even more preferably, by using isopropanol.

[0070] In detailed embodiments, the network of nanowires is produced at a rate of at least 0.01 g / h; preferably at a rate of at least 0.02 g / h; more preferably at a rate of at least 0.05 g / h; and even more preferably at a rate of about 0.1 g / h.

[0071] In another detailed embodiment, the nanowire network is generated at a rate between 0.01 g / h and 10 g / h; preferably at a rate between 0.02 g / h and 5 g / h; more preferably at a rate between 0.05 g / h and 1 g / h; and even more preferably at a rate between 0.09 g / h and 1 g / h.

[0072] Step (b) Step (b) of the method for preparing an electrode of the present invention is directed to coating the network of nanowires obtained from step (a) with a carbon coating by pyrolysis of a carbon precursor at a temperature between 500°C and 1300°C under an inert gas atmosphere.

[0073] The coating in step (b) is formed when a carbon precursor decomposes in an inert gas atmosphere at a temperature between 500°C and 1300°C to produce pyrolytic carbon, which deposits on the nanowire network to form a carbon coating.

[0074] The carbon precursor in step (b) can be any compound known in the art that decomposes under an inert gas atmosphere at a temperature between 500° C. and 1300° C. to yield pyrolytic carbon. Non-limiting examples of carbon precursors include organic molecules such as hydrocarbons, e.g., acetylene.

[0075] In a detailed embodiment, step (b) of the method of preparing an electrode of the present invention is carried out at a temperature between 550°C and 1200°C; preferably between 600°C and 1100°C; preferably between 620°C and 1000°C; more preferably between 650°C and 900°C; even more preferably between 660°C and 850°C; and even more preferably at about 700°C.

[0076] Step (b) of the method for preparing an electrode of the present invention is carried out under an inert gas atmosphere, which may be a noble gas atmosphere or N 2 Under an atmosphere; e.g., any noble gas or N 2 A sheath gas selected from the group consisting of Ar and N. 2 more preferably, it means that it may be carried out using a gas flow containing Ar.

[0077] In more detailed embodiments, the carbon precursor is a hydrocarbon or mixture of hydrocarbons; preferably, the hydrocarbon or mixture of hydrocarbons comprises hydrocarbons having less than 10 carbon atoms; more preferably, less than 9, less than 8, less than 7, less than 6, less than 5, less than 4, or less than 3 carbon atoms.

[0078] Non-limiting examples of hydrocarbons suitable as carbon precursors are methane, ethane, ethylene, acetylene, propane, propylene, methylacetylene, cyclopropane, propadiene, butane, butyne, cyclobutane, butadiene, pentane, pentene, pentyne, cyclopentane, pentadiene, hexane, hexane, hexyne, cyclohexane, hexadiene, or mixtures thereof; preferably, methane, ethane, ethylene, acetylene, propane, propylene, methylacetylene, cyclopropane, propadiene, butane, butyne, cyclobutane, butadiene, pentane, pentene, pentyne, cyclopentane, pentadiene, and mixtures thereof; more preferably, methane, ethane, ethylene, acetylene, propane, propylene, methylacetylene, cyclopropane, propadiene, butane, butane, butyne, cyclobutane, butadiene, and mixtures thereof.

[0079] In more particular embodiments, the carbon precursor is in gas or vapor phase; preferably a gas.

[0080] In one embodiment, step (b) is carried out in the same reaction vessel as step (a).

[0081] In a more particular embodiment, the carbon precursor is part of an additional gas stream introduced into the reaction vessel in step (a); preferably one which further comprises an inert gas.

[0082] In particular embodiments, the carbon precursor is at least 1% by volume of the total volume of the gas stream; preferably at least 2%; more preferably at least 3%; even more preferably at least about 5%.

[0083] Without wishing to be bound by theory, the authors have determined that, as a consequence of the carbopyrolytic deposition step of the electrode synthesis method, the carbon coating of the electrode of the invention contains crystalline graphitic domains that improve the electrochemical properties of said electrode, in particular its electrical conductivity. Furthermore, the interface between the nanowires of the network and the carbon coating contains mainly aligned crystalline graphitic domains that improve the final properties of the electrode.

[0084] In a detailed embodiment, step (b) further comprises drying the nanowires coated with the carbon coating; preferably at a temperature between 80°C and 150°C; more preferably at a temperature between 90°C and 140°C; and even more preferably at a temperature of about 120°C.

[0085] In one embodiment, the drying step is carried out under vacuum.

[0086] In another embodiment, the drying step is carried out for at least 4 hours; preferably at least 6 hours.

[0087] In a detailed embodiment, step (b) comprises compressing the nanowires coated with the carbon coating; preferably, mechanically compressing the nanowires coated with the carbon coating; more preferably, compressing the nanowires by 10 5 Pa and 10 10 Between 10 Pa, preferably 10 6 Pa and 10 9 between about 10 Pa; more preferably between about 10 8 The method further comprises applying a pressure of 100 Pa.

[0088] Step (c) The method of the invention optionally comprises the further step (c) of contacting the network of nanowires coated with the carbon coating with an electrical connection or current collector.

[0089] In one embodiment, the electrical connections or current collectors comprise an electrically conductive material such as a metallic material, for example a metal wire. The electrical connections in the previous embodiment may be made by any method known in the art.

[0090] electrode As mentioned above, in a second aspect, the present invention provides a method for producing a composition comprising the steps of: - a network of nanowires coated with a carbon coating; the network of nanowires has a nanowire aspect ratio of at least 130; the carbon coating comprises graphitic carbon; a network of nanowires, the carbon coating being in an amount greater than 3 wt.% of the total weight of the network of nanowires coated with the carbon coating; - optionally electrical connections and / or current collectors, The present invention is directed to an electrode obtainable by the method of any of the detailed embodiments of the method of the present invention, including

[0091] In a detailed embodiment, the nanowires of the nanowire network of the electrode of the invention form a mesh; preferably, the nanowires of the nanowire network are bonded, entangled, connected, fused or interlocked between each other; preferably bonded, entangled, connected or fused; more preferably, bonds are formed between them. In one embodiment, the mesh comprises aggregates of nanowires. In a detailed embodiment, the mesh is free-standing.

[0092] In a detailed embodiment, the nanowire network is free-standing. In the context of the present invention, the term "free-standing" refers to a structure that is not supported by another body or structure, such as a substrate. In one embodiment, the nanowire network does not include an additional phase, such as an additional matrix or binder. In an alternative embodiment, the nanowire network consists of nanowires.

[0093] In particular embodiments, the nanowires of the network of the electrodes of the invention are aggregated; in particular they are strongly aggregated; in particular they are strongly aggregated by secondary forces such as van der Waals forces, permanent dipoles, hydrogen bonds, and / or covalent bonds, entanglements, and other forms of mechanical interlocking. By strongly aggregated, in the context of the present invention, it is implied that the material forms a solid object, and that the nanowires comprising the network cannot be easily dispersed without resorting to sonication, stirring, cutting, or similar methods.

[0094] In a particular embodiment, the network of nanowires of the electrode of the invention is a continuous network, in the context of the present invention a continuous network is understood as a non-discrete percolated network.

[0095] In a particular embodiment, the nanowire network of the present invention is an aerogel, i.e., of low density; -2 g / cm 3 less than; preferably 10 -3 g / cm 3 less than; more preferably 10 -4 g / cm 3 less than; more preferably 10 -5 g / cm 3 In a detailed embodiment, the nanowire network of the present invention has a mass of at least 0.001 g / cm. 3 of; in detail at least 0.01g / cm 3 has a density of

[0096] In more particular embodiments, the nanowire network of the electrode of the present invention is densified; particularly, it is densified by mechanical, solvent addition, electromagnetic, or similar methods.

[0097] In particular embodiments, the nanowires of the networks of the invention have an average aspect ratio (length / diameter) of at least 135; more preferably 140; more preferably 150; even more preferably 200; and even more preferably 250.

[0098] In more particular embodiments, the nanowires of the networks of the invention have an average aspect ratio (length / diameter) between 135 and 1000; particularly between 140 and 800; more particularly between 150 and 700. The average aspect ratio of the nanowires of the networks of the invention may be calculated from the average of values ​​obtained by measuring the dimensions of a substantial number (e.g., more than 100) of nanowires using electron microscopy.

[0099] In particular embodiments, the average length of the nanowires of the networks of the invention is at least 1 micron; particularly at least 2 microns; preferably at least 3, 4, or 5 microns; more preferably at least 10 microns. In particular embodiments, the average length of the nanowires of the networks of the invention is between 1 micron and 30 microns; preferably between 2 microns and 20 microns; more preferably between 3 microns and 15 microns. The average length of the nanowires of the networks of the invention may be calculated from the average of values ​​obtained by measuring the length of more than 100 nanowires using electron microscopy.

[0100] In a particular embodiment, the nanowires of the nanowire network of the electrode of the present invention are Al x Ga 1-x As y P 1-y , AlN, Al z Ga x In 1-x-z N, Si, SiC, Ge or Si x Ge 1-x , SiO x , TiO x , ZnO x , Ta x , MoS y , W.S. y , MoTe y ,TaSe y , NbSe y , NiTe y , BN, Cu, Pt, CoO x , MnO x , CuO x , V.O.x , Li x Mn y O, Li x Ni y Mn z O, and Ni x wherein 0≦x≧1, 0≦y≧1, and 0≦z≧1; preferably, Si, SiC, Ge or Si x Ge 1-x , and SiO x and 0≦x≧1; more preferably, Si, Ge or Si x Ge 1-x , and SiO x and 0≦x≧1; more preferably, it contains Si or Ge; and even more preferably, it contains Si.

[0101] In another detailed embodiment, the nanowires of the network of nanowires of the electrode of the invention are Al x Ga 1-x As y P 1-y , AlN, Al z Ga x In 1-x-z N, Si, SiC, Ge or Si x Ge 1-x , SiO x , TiO x , ZnO x , Ta x , MoS y , W.S. y , MoTe y ,TaSe y , NbSe y , NiTe y , BN, Cu, Pt, CoO x , MnO x , CuO x , V.O. x , Li x Mn y O, Li x Ni y Mn z O, and Ni x and 0≦x≧1, 0≦y≧1, and 0≦z≧1; preferably, Si, SiC, Ge or Six Ge 1-x , and SiO x and 0≦x≧1; more preferably, Si, Ge or Si x Ge 1-x , and SiO x and 0≦x≧1; more preferably, it contains Si or Ge; and even more preferably, it contains Si.

[0102] In a particular embodiment, the nanowires of the nanowire network of the electrode of the present invention are Al x Ga 1-x As y P 1-y , AlN, Al z Ga x In 1-x-z N, Si, SiC, Ge or Si x Ge 1-x , SiO x , TiO x , ZnO x , Ta x , MoS y , W.S. y , MoTe y ,TaSe y , NbSe y , NiTe y , BN, Cu, Pt, CoO x , MnO x , CuO x , V.O. x , Li x Mn y O, Li x Ni y Mn z O, and Ni x and wherein 0≦x≦2, 0≦y≦2, and 0≦z≦2; preferably, Si, SiC, Ge, or Si x Ge 1-x , and SiO x and 0≦x≦2; more preferably, Si, Ge or Si x Ge 1-x , and SiO x and 0≦x≦2; more preferably, it contains Si or Ge; and even more preferably, it contains Si.

[0103] In a particular embodiment, the nanowires of the nanowire network of the electrode of the present invention are Al x Ga 1-x As y P 1-y , AlN, Al z Ga x In 1-x-z N, Si, SiC, Ge or Si x Ge 1-x , SiO x , TiO x , ZnO x , Ta x , MoS y , W.S. y , MoTe y ,TaSe y , NbSe y , NiTe y , BN, Cu, Pt, CoO x , MnO x , CuO x , V.O. x , Li x Mn y O, Li x Ni y Mn z O, and Ni x and wherein 0≦x≦2, 0≦y≦2, and 0≦z≦2; preferably, Si, SiC, Ge, or Si x Ge 1-x , and SiO x and 0≦x≦2; more preferably, Si, Ge or Si x Ge 1-x , and SiO x and 0≦x≦2; more preferably, it contains Si or Ge; and even more preferably, it contains Si.

[0104] In a detailed embodiment, the nanowire network of the electrode of the present invention has a density of at least 0.01 g / cm 3 of; in detail at least 0.05g / cm 3 of; more particularly at least 0.075 g / cm 3 of; more specifically at least 0.080 g / cm 3Preferably at least 0.015 g / cm 3 more preferably at least 0.020 g / cm 3 more preferably about 0.128 g / cm 3 It has a volume density of

[0105] In a particular embodiment, the nanowire network of the electrode of the present invention has a density of 0.01 g / cm 3 and 0.2g / cm 3 between; specifically 0.07g / cm 3 and 0.30 g / cm 3 The volume density of the nanowire networks of the present invention may be calculated from any experimental technique known in the art, in particular it is determined from the area density and thickness of a sample of the nanowire network.

[0106] In a detailed embodiment, the nanowires of the network of nanowires are entangled; preferably physically entangled.

[0107] In particular embodiments, the network of nanowires is a network that includes nanowires. In particular embodiments, the nanowires forming the network can have the same or different properties. In more particular embodiments, the nanowires included in the network have different compositions and / or aspect ratios.

[0108] In particular embodiments, the nanowires of the network of nanowires are hollow (i.e., they are nanotubes); preferably, they are nanotubes. In more particular embodiments, the hollow nanowires are made of Si, SiC, Ge or Si. x Ge 1-x , and SiO x where 0≦x≦2; more preferably, the material is made of at least one material selected from Si and Ge; and even more preferably, the material is made of Si.

[0109] In particular embodiments, the network of nanowires further comprises metallic catalyst particles; particularly the metallic catalyst particles of the methods of the present invention.

[0110] In particular embodiments, the nanowire networks of the present invention further comprise particles; preferably quasi-spherical particles; more preferably quasi-spherical amorphous particles.

[0111] In a particular embodiment, the network of nanowires comprises nanowires and catalyst particles, and optionally particles; in particular for example quasi-spherical particles or spherical particles, the quasi-spherical particles being the result of pyrolysis of the precursor compounds of the method of step (a).

[0112] In a detailed embodiment, the nanowires of the network of nanowires further comprise a labeling or marking element or compound; said labeling element or compound provides traceability of the nanowires. In a detailed embodiment, the labeling or marking of the nanowires is carried out during the synthesis process or in an additional step after said synthesis.

[0113] In a detailed embodiment, the nanowires of the network of nanowires are primarily aligned.

[0114] In detailed embodiments, the nanowires of the nanowire network are aligned by electromagnetic, electrochemical, fluidic, or other methods.

[0115] In one embodiment, the nanowire network of the electrode of the invention comprises a crystalline phase and an amorphous phase; preferably, the crystalline phase is present in at least 50 wt% of the total weight of the network; more preferably, at least 75 wt%; even more preferably, at least 90 wt%; and more preferably, the crystalline phase comprises crystalline nanowires and the amorphous phase comprises amorphous particles; preferably, amorphous spherical particles.

[0116] In one embodiment, the nanowire network of the present invention comprises at least 50 wt%; preferably at least 75 wt%; more preferably at least 80 wt%; more preferably at least 90 wt% crystalline nanowires of the total weight of the network.

[0117] In one embodiment, the nanowires of the network of nanowires are crystalline.

[0118] In one embodiment, the network of nanowires has an energy-to-break value of at least 0.05 J / g; preferably between 0.1 J / g and 0.5 J / g. The energy-to-break value is measured by mechanical tensile testing of the network of nanowire samples using conventional mechanical testing equipment as known in the art.

[0119] In one embodiment, the network of nanowires has a specific tensile strength greater than 0.5 MPa / SG; preferably greater than 0.8 MPa / SG, more preferably greater than 1 MPa / SG. In particular, specific tensile strength values ​​are in MPa / SG, where SG is g / cm. 3 By specific tensile strength is meant the specific gravity, numerically equivalent to the density of the nanowire network, in units of tensile strength. Specific tensile strength may be measured by any tensile testing technique known in the art, for example by mechanical tensile measurement of a sample of the nanowire network using a Textechno Favimat tensile tester at a strain rate of 10% / min and preferably with a gauge length of 5 mm.

[0120] Carbon Coating In the context of the present invention, the expression "carbon coating" is intended to refer to a carbon-based coating; in particular, said carbon coating is obtained after step (b) of the method of the invention by pyrolyzing a carbon precursor under an inert gas atmosphere at a temperature between 500°C and 1300°C to obtain a network of nanowires coated with a carbon coating.

[0121] In one embodiment, the carbon coating is in an amount greater than 3 wt% of the total weight of the network of nanowires coated with the carbon coating; preferably greater than 5 wt%; preferably greater than 6, 7, or 8 wt%; more preferably greater than 10 wt%; more preferably greater than 12 wt%; and even more preferably greater than 15 wt%.

[0122] In one embodiment, the carbon coating is in an amount of more than 3 wt% and less than 50 wt% of the total weight of the network of nanowires covered with the carbon coating, preferably more than 5 wt% and less than 49 wt%; preferably more than 5, 6, 7, or 8 wt% and less than 45, 46, 47 wt%; more preferably more than 10 wt% and less than 40 wt%; more preferably more than 12 wt% and less than 38 wt%; and even more preferably more than 15 wt% and less than 35 wt%.

[0123] In one embodiment, the carbon coating is in an amount of about 27 wt% of the total weight of the network of nanowires coated with the carbon coating.

[0124] The carbon coating includes graphitic carbon.

[0125] In one embodiment, the carbon coating is comprised of graphitic carbon and non-graphitic carbon, such as amorphous carbon.

[0126] In a detailed embodiment, the graphitic carbon of the carbon coating comprises carbon graphitic planes that are aligned with the crystallographic planes of the nanowire at the interface between the carbon coating and the nanowire.

[0127] In a more particular embodiment, when the nanowire is a Si nanowire, the graphitic (002) basal plane of the graphitic carbon of the carbon coating is oriented parallel to the Si(111) plane of the Si nanowire at the interface between the carbon coating and the nanowire.

[0128] In the context of the present invention, the expression "graphitic carbon" is understood as any type of material consisting of elemental carbon in the allotropic form of graphite, regardless of the presence of structural defects or stacking disorders. The presence of graphitic carbon on a sample may be detectable by diffraction methods known in the art.

[0129] In one embodiment, the electrodes of the invention have a porosity of between 60% and 90%, particularly between 65% and 85%, more particularly between 70% and 80%, and even more particularly about 78%. The porosity of the electrodes was measured using methods known in the art, such as by determining the volume of a routine sample by optical and / or electron microscopy and measuring its weight gravimetrically.

[0130] In one embodiment, the electrode of the present invention has a viscosity of 0.05 g / cm 3 and 0.70 g / cm 3 between 0.10 g / cm 3 and 0.65 g / cm 3 between 0.40 g / cm 3 and 0.60 g / cm 3 between 0.51 g / cm 3 The bulk density was measured by gravimetrically determining the mass and dividing it by the volume of the electrode.

[0131] In one embodiment, the electrodes of the invention are electrically conductive. In a more detailed embodiment, the electrodes of the invention have in-plane and out-of-plane electrical conductivities ranging from 1-1.5 S / m and 0.1 to 0.6 S / m, respectively. The electrical conductivity of the electrodes was measured as known in the art by two-probe electrical resistance measurements using a flat metal tape contact surface.

[0132] cell In a further aspect, the present invention provides a method for producing a method for treating a cancer cell comprising: - electrodes, at least one of which is according to any of the embodiments of the present invention; - electrolytes; - a means for connecting to a power / load source; Target cells that contain

[0133] In one embodiment, the electrolyte of the cell of the invention comprises lithium, hi a detailed embodiment, the cell is a lithium battery, preferably a lithium ion battery.

[0134] In one embodiment, at least one electrode is a working electrode, hi another embodiment, at least one electrode is an anode.

[0135] In another embodiment, the electrolyte of the cell is a gel electrolyte, hi another embodiment, the electrolyte of the cell is a solid.

[0136] use A further aspect of the invention is directed to the use of the electrode of the invention in any of its detailed embodiments in a battery, preferably a lithium battery; more preferably a lithium ion battery.

[0137] A further aspect of the invention is directed to a method of storing or supplying electricity comprising the step of using an electrode of the invention in any of its detailed embodiments in a battery, preferably in a lithium battery; more preferably in a lithium ion battery.

[0138] It is to be understood that the scope of the present disclosure includes all possible combinations of the embodiments disclosed herein. EXAMPLES

[0139] The present invention is illustrated by the following examples, which are not intended to limit the scope of the invention in any way.

[0140] Example 1: Electrodes The electrodes were fabricated by coating a network of nanowires, including silicon (Si) nanowires, with a uniform carbon coating.

[0141] Nanowire networks, including silicon (Si) nanowires, were produced by decomposing a Si precursor in the presence of catalytic nanoparticles suspended in a gas stream in a reaction vessel. In particular, Si nanowire networks were synthesized by floating catalyst chemical vapor deposition (FCCVD) at 650 °C using a continuous flow of an aerosol of gold nanoparticles as catalyst, silane as precursor, and a mixture of nitrogen and hydrogen as carrier gas. The gas molar fraction was 18:31:1 (N 2 :H 2 :SiH 4 ) The reaction vessel used was a metal reaction tube in a tubular furnace.

[0142] After the synthesis of the Si nanowire network, the network was coated with carbon by pyrolysis of acetylene gas (5% by volume in Ar) at 700 °C to form an electrode. The mass fraction of carbon in the electrode (nanowire network and carbon coating) was determined gravimetrically using a 5-digit high-precision weighing balance. The carbon-coated Si nanowire network was then dried overnight at 120 °C under vacuum and pressed at room temperature using a simple press for 10 min. 8 The result is a fully formed electrode.

[0143] Figure 1 shows images of free-standing Si nanowire networks before (a) and after (b) carbon coating.

[0144] Mechanical testing results (not shown here) showed that the electrode was flexible in bending due to its network structure, giving it mechanical properties similar to other fibrous solids such as paper, with a strain at break of over 10% and an average specific strength of 1.2 MPa / SG. Due to its mechanical robustness, the carbon-coated Si nanowire network was directly integrated with a copper current collector without the need for a polymer binder or other form of mechanical reinforcement, as is the case for other granular electrodes.

[0145] Figure 2 shows an electron micrograph of the Si nanowire network before carbon coating. Figure 3 shows an HRTEM micrograph of the interface between the carbon coating and the crystalline Si nanowires of the Si nanowire network after carbon coating. The results in Figure 3 show the preferential ordering of the carbon graphitic planes at the interface between the carbon coating and the Si nanowires. In addition, Figure 4 shows a representative Raman spectrum showing the crystallinity of the Si nanowires and graphitization of the coating on the carbon-coated Si nanowire network. Figure 5 shows the crystalline SiO 2 1 shows an XRD pattern indicating the absence of

[0146] The average length of the nanowires in the resulting nanowire network was at least 2 microns. The average diameter and aspect ratio of the nanowires were obtained from a number of measurements performed by image analysis of scanning electron micrographs at high magnification. The length of the nanowires was calculated from the product of the diameter and the aspect ratio. In addition, the nanowires of the nanowire network are crystalline. The sample contains more than 66.5 wt. % crystalline Si nanowires, based on the total weight of the carbon-coated nanowire network (i.e., electrode excluding current collector).

[0147] Analysis of the samples by electron microscopy showed a C coating with an average thickness of 3.8 ± 1.3 nm, which is uniform across the entire electrode. The carbon coating of the Si network was a combination of graphitic and amorphous domains. Small stacking of the graphitic planes is directly observable by high-resolution transmission electron microscopy (Figure 3). 2 The high degree of hybridization was also confirmed by the relatively narrow G band in the Raman spectrum (Figure 4). In addition, the passivating SiO 2No layers were found. Instead, the interface between the silicon nanowires of the network and the carbon coating contains crystalline silicon and mainly aligned crystalline graphitic domains. In addition, the graphitic (002) basal plane of the coating was found to be oriented parallel to the Si(111) surface of the nanowires and thus tilted with respect to the longitudinal axis of the silicon nanowires, as shown for example in Figure 3. The authors attribute the carbopyrolysis step of the electrode synthesis method to the chemical reduction of the silicon nanowire surface and the deposition of nucleation-assisted graphitic carbon surfaces on the crystalline silicon nanowires.

[0148] Gravimetric measurements showed that the mass fraction of the carbon coating averaged about 27 wt% of the total mass of the silicon nanowire network and the carbon coating. The volume density of the electrode was 0.51 g / cm. 3 The in-plane electrical conductivity (σ IP ) and out-of-plane electrical conductivity (σ OOP ) range from 1 to 1.5 S / m and 0.1 to 0.6 S / m, respectively. Two-probe electrical resistance measurements were performed on the electrode samples using a flat copper tape contact surface. The high electrical conductivity values ​​obtained are a result of the high uniformity and high graphitization of the carbon coating.

[0149] Thus, the results show that the performed pyrolysis reaction can effectively coat the Si nanowire networks with a thin (e.g., low mass fraction) uniform carbon layer, providing high electrical conductivity values.

[0150] In contrast, electrodes containing only a network of nanowires and electrical connections or current collectors (without a carbon coating) have much lower electrical conductivity values.

[0151] By comparing with other carbon materials such as carbon black, graphene, or carbon nanotubes, the authors confirm that denser samples may require larger amounts of such materials to reach electrical conductivity values ​​similar to the coated electrodes of the present invention.

[0152] Sample characterization The samples were characterized using field-effect scanning electron microscopy (FESEM, FEI Helios NanoLab 600i, simultaneously imaging using TLD and CBS detectors), transmission electron microscopy (TEM, Talos F200X FEG, 200 kV), Raman spectroscopy (Ranishaw, using a 532 nm laser source), and 2D wide-angle X-ray scattering (WAXS) and small-angle X-ray scattering (SAXS). WAXS / SAXS data were collected using a microfocus spot with a diameter of about 10 μm and a radiation wavelength of λ = 1.0 Å. The collected patterns were corrected for background scattering and shown after azimuthal integration.

[0153] Electrochemical performance The performance of the above electrodes was investigated in two-electrode as well as three-electrode cell configurations using a bioelectrochemical workstation (VMP300) and a Neware battery tester (CT-4008-5V10mA-164).

[0154] A coin-type cell (CR 2032) was assembled using the above carbon-coated Si nanowire network as the working electrode, a circular lithium foil as the counter electrode, a Whatman GF / D disk facing the working electrode and a PP membrane (25 um) as the separator, and 1 M LiPF6 and 10 wt% fluoroethylene carbonate (FEC) in ethylene carbonate / diethyl carbonate (1:1 v / v, Solvionic) as the electrolyte.

[0155] The cell was cycled galvanostatically at C rates of C / 20 to 2C, Li / Li +The samples were characterized by cyclic voltammetry at scan rates of 0.1–10 mV / s in the voltage window of 1.5–0.01 V vs. Li. For galvanostatic measurements, 1C was 15 S 4 The cell was also driven at 10 MHz with an AC amplitude of 10 mV. -2 They were characterized using electrochemical impedance spectroscopy in the MHz frequency window, and the specific capacitance values ​​are normalized to the mass of silicon.

[0156] Figure 6 shows (a) the voltammograms of the first 10 cycles at a scan rate of 0.025 mV / s and (b) the rate performance (specific capacity vs. cycle number) at C rates from C / 20 to 2C obtained using carbon-coated Si nanowire networks as electrodes in a half-cell. Electrode mass loading: 1.2 mg / cm 2 .

[0157] In detail, Figure 6 b shows the rate performance of carbon-coated Si nanowire networks as electrodes in half-cells compared for two different C contents (i.e., weight percentages of carbon relative to the total weight of the nanowire network and carbon coating of 5% (triangles) and 27% (circles)) at C rates ranging from C / 20 (≈0.179 mA / g) to 2C (≈7.2 mA / g).

[0158] The results (see Fig. 6(b)) show that for both Si nanowire network electrodes with different C coating amounts, the first discharge (lithiation) capacity, including the solid electrolyte interphase (SEI) formation, was 4200 mAh / g (Li 4.4The results showed that the specific capacity of the optimized electrode (with 27 wt% carbon coating) exceeded the theoretical capacity of the Si at C / 20 (1C is 3.6 A / g) and remained steady after SEI formation, while the capacity of the electrode with 5 wt% carbon coating decreased to 2500 mAh / g at the second cycle and to 1280 mAh / g after 5 cycles, as seen in Figure 6. The specific capacity of the optimized electrode with 27 wt% carbon coating was significantly higher at all c-rates.

[0159] The initial coulombic efficiency (ICE, illustratively the ratio of charge capacity to discharge capacity in the first cycle) of a Si nanowire network coated with 27 wt% carbon and acting as an electrode was estimated to be about 72%, whereas for a Si nanowire network with only a 5 wt% C coating, it is about 55%.

[0160] The anode of a Si nanowire network coated with 27 wt % of the carbon coating of the present invention tested in a half cell had a capacitance of 3.1 mg / cm 2 High areal density (9.3mAh / cm 2 ), it was demonstrated that the capacity was close to the theoretical capacity (3041 mAh / g) at low rates.

[0161] The electrochemical stability of the electrode was tested. Figure 7 shows the specific capacity (i) as well as the coulombic efficiency (ii) of the carbon-coated Si nanowire network as an electrode at C-rate versus cycle number: (a) C / 10 for 100 cycles and (b) C / 2 for 500 cycles. The results show that at C / 10 rate, after 100 charge-discharge cycles, the material maintains 75% of the initial capacity, while the coulombic efficiency increases from 97.6% to 99.1%. At a faster charge-discharge rate of C / 2, the material maintains about 60% of the initial capacity, while the coulombic efficiency increases from 98.8 to 99.9%. Therefore, it is concluded that the optimized electrode of the present invention exhibits high stability along with high initial specific capacity.

[0162] Example 2: Comparative Example In a comparative example, an electrode was fabricated consisting of a network of nanowires including silicon (Si) nanowires synthesized as described in Example 1, except that the nanowires were without the carbon coating and without the interspersed carbon nanotubes, which act as an electrically conductive additive.

[0163] In this example, the electrodes were prepared by drop-casting an aqueous dispersion of carbon nanotubes onto the Si nanowire network. The aqueous dispersion consisted of a standard commercial mixture of single-walled carbon nanotubes in water. After drop-casting the carbon nanotube dispersion, the electrodes were dried overnight at 120° C. in an electric vacuum oven and immediately transferred to a glove box and assembled into coin cells similar to those described in Example 1. The mass fraction of SWCNTs in the electrodes was estimated based on the drop-cast volume to be 2.5 wt.% of the total electrode weight.

[0164] Figure 8 shows a comparison of the rate performance of Si nanowire networks coated with carbon coatings (circles) and Si nanowire networks with interspersed carbon nanotubes (squares) as electrodes in half-cells at C-rates ranging from C / 20 (≈0.179 mA / g) to 2C (≈7.2 mA / g).

[0165] The results in FIG. 8 showed that the specific capacitance at all rates was significantly lower for the Si nanowire network anode with interspersed carbon nanotubes compared to the Si nanowire network anode with carbon coating.

Claims

1. (a) i. providing a first gas stream to a reaction vessel; the first gas flow comprises at least one precursor compound comprising at least one element selected from Si, Ge, Al, Cu, Zn, Sb, Ni, Ti, Se, Ta, Pt, Mo, V, W, Co, Mn, and Li; the at least one precursor compound is a metal hydride or an organometallic compound; ii. providing a second gas stream to the reaction vessel, the second gas stream comprising metallic catalyst particles; the first and second gas streams mix in the reaction vessel to form a gas stream mixture; the metallic catalyst particles comprising one or more elements selected from Au, Ag, Cu, Fe, Ni, Ga, Co, Pt, In, and Al; and producing a network of nanowires by a method comprising: said at least one precursor compound is present in said gas stream mixture at a mole fraction (xi) of at least 0.010; the temperature in the reaction vessel is in the range of 200 to 3000° C.; the at least one precursor compound decomposes under temperature in the reaction vessel and grows on the metallic catalyst particles by vapor-liquid-solid (VLS) and / or chemical vapor deposition (CVD) to form a network of nanowires; (b) coating the network of nanowires obtained from step (a) by pyrolysis of a carbon precursor at a temperature between 500° C. and 1300° C. under an inert gas atmosphere to obtain a network of nanowires covered with a carbon coating; (c) optionally contacting the network of nanowires covered with the carbon coating with an electrical connection or current collector; A method for manufacturing an electrode comprising:

2. 2. The method of claim 1, wherein the at least one precursor compound of step (a) comprises an element selected from Si and Ge.

3. The at least one precursor compound of step (a) is selected from the group consisting of (3-aminopropyl)triethoxysilane, N-sec-butyl(trimethylsilyl)amine, chloropentamethyldisilane, tetramethylsilane, silicon tetrabromide, silicon tetrachloride, tris(tert-butoxy)silanol, SiH 4 3. The method of claim 1 or 2, wherein the germanium hydride is selected from the group consisting of tetramethylgermanium, triethylgermanium hydride, triphenylgermanium hydride, triphenylgermanium hydride, tetramethylgermanium, tributylgermanium hydride, triethylgermanium hydride, and triphenylgermanium hydride.

4. 4. The method according to any one of claims 1 to 3, wherein the metallic catalyst particles of step (a) are gold particles; preferably gold particles having a diameter between 0.1 nm and 100 nm.

5. The gas stream mixture of step (a) is H 2 and / or the inert atmosphere of step (b) comprises argon or nitrogen gas.

6. 6. The method according to any one of claims 1 to 5, wherein the carbon precursor of step (b) is an organic molecule; preferably a hydrocarbon.

7. - a network of nanowires coated with a carbon coating; the network of nanowires has a nanowire aspect ratio of at least 130; the carbon coating comprises graphitic carbon; a network of nanowires, the carbon coating being in an amount greater than 3 wt. % of the total weight of the network of nanowires coated with the carbon coating; - optionally electrical connections and / or current collectors, 7. An electrode obtainable by the method according to claim 1 , comprising:

8. The nanowire composition is Si, SiC, Ge, Si x Ge 1-x , SiO x , Al x G 1-x AsyP 1-y , Al z G x In 1-x-z N, AlN, Cu, CuO x , ZnO x , GaSb, Ga x In 1-x A.S. y Sb 1-y , NiTe y , Li x Ni y Mn z O, Ni x , TiO x , NbSe y , Ta x , TaSe y , Pt, MoTe y , MoS y , V.O. x , W.S. y , CoO x , MnO x , Li x Mn y O, and Li x Ni y Mn z O; 0≦x≧1, 0≦y≧1, and 0≦z≧1; preferably the nanowires are Si, SiC, Ge or Si x Ge 1-x , and SiO x 8. The electrode of claim 7, wherein 0≦x≧1.

9. the nanowires of the network of nanowires are crystalline; 9. The electrode of claim 7 or 8, wherein the carbon coating is in an amount of at least 5 wt% of the total weight of the network of nanowires coated with the carbon coating.

10. The electrode of claim 9 , wherein the graphitic carbon of the carbon coating comprises carbon graphite faces aligned with crystallographic planes of the nanowire at the interface between the carbon coating and the nanowire.

11. the carbon coating has a thickness between 1 nm and 10 nm; and / or The carbon coating has a thickness of 0.05 g / cm 3 and 0.70 g / cm 3 11. The electrode of claim 7, having a volumetric density of between 0.01 and 0.5, the volumetric density being measured by gravimetrically determining the mass and dividing this by the volume of the electrode.

12. a network of nanowires coated with a carbon coating and, optionally, electrical connections or current collectors; and / or 12. The electrode of claim 7, wherein the carbon coating consists of graphitic carbon and amorphous carbon.

13. - electrodes, at least one of which is according to any one of claims 7 to 12; - an electrolyte; - means for connecting to a power / load source; The cell that contains

14. 14. The cell according to claim 13, wherein the electrode according to any one of claims 7 to 12 is a working electrode.

15. 15. The cell of claim 12 or 14, wherein the electrolyte comprises lithium.

16. Use of an electrode according to any one of claims 7 to 12 in a battery; preferably in a lithium battery.